Empowering Communities, Transforming Health: A Simulation-Based Approach to Optimizing Posyandu Management - Yudhana, Affiandra; Novianty, Della; Rahma Sarita, Fitria Nur; Michael Kevin Widianto, Michael Kevin Widianto; Rizal Hermawan, Muhammad Riansyah; Humairo, Mika Vernicia (Inovasi Lokal, 2025)
Community-based Posyandu (Integrated Health Posts) programs are vital for improving public health outcomes in underserved areas, yet many face challenges such as low participation and resource limitations. This study employed a simulation-based approach to evaluate strategies for enhancing Posyandu effectiveness, focusing on three key interventions: empowering health cadres and community leaders, adjusting schedules to align with community needs, and adding supplementary services such as maternal health consultations and child nutrition checks. The results demonstrated that supplementary services had the most significant impact, increasing participation rates to 75%, followed by community mobilization (60%) and flexible scheduling (55%). These findings highlight the importance of offering value-added services, fostering trust through local leaders, and ensuring inclusivity through adaptable schedules. Continuous health education further reinforced awareness and voluntary participation. However, challenges such as resource allocation, training, and scalability remain critical. Leveraging digital tools like mobile applications and electronic health records offers innovative solutions to streamline operations and enhance efficiency. The study concludes that a holistic, community-driven approach is essential for strengthening Posyandu programs, ensuring equitable access to quality healthcare while remaining adaptable to diverse contexts.